X-ray Free Electron Lasers A Revolution in Structural Biology - Boutet, Sébastien; Fromme, Petra; Hunter, Mark S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The timely volume describes recent discoveries and method developments that have revolutionized Structural Biology with the advent of X-ray Free Electron Lasers. It provides, for the first time, a comprehensive examination of this cutting-edge technology. It discusses of-the-moment topics such as growth and detection of nanocrystals, Sample Delivery Techniques for serial femtosecond crystallography, data collection methods at XFELs, and more. This book aims to provide the readers with an overview of the new methods that have been recently developed as well as a prospective on new methods under development. It highlights the most important and novel Structural Discoveries made recently with XFELS, contextualized with a big-picture discussion of future developments.
X-ray Free Electron Lasers and their applications -- Serial Femtosecond Crystallography (SFX): An Overview -- Small is Beautiful: Growth and Detection of Nanocrystals -- The lipid cubic phase as a medium for the growth of membrane protein microcrystals -- Sample Delivery Techniques for Serial Crystallography -- When diffraction stops and destruction begins -- Climbing the data mountain: processing of SFX data -- Phasing XFEL serial crystallography data -- Structure Determination by Continuous Diffraction from Imperfect Crystals -- Advances in structure determination of G protein-coupled receptors by SFX -- Time-resolved serial femtosecond crystallography, towards molecular movies of biomolecules in action -- Towards Molecular Movies of Enzymes -- X-ray Spectroscopy with XFELs -- Single molecule imaging using X-ray free electron lasers -- The use of angular correlations to extract 3-dimensional structural information from X-ray solution scattering -- Future Directions of High Repetition Rate X-rayFree Electron Lasers -- Index.
Keywords: Biotechnology; Spectrum analysis; Chemical Bioengineering; Spectroscopy